Features of the Use of Digital Educational Technologies During the COVID-19 Pandemic - Flera Ya. KHABIBULLINA; Iraida G. IVANOVA; Nikolaj A. KIRILLOV; Nadezhda SMIRNOVA (Communications of International Proceedings, 2020)
The article is devoted to a comparative analysis of digital educational technologies used in Russian educational institutions at different levels in the conditions of self-isolation caused by the coronavirus pandemic in the world. Based on the analysis of the results of the study, the authors conclude that the pandemic accelerated the transition to distance learning and at the same time exposed pedagogical, psychological and medical problems associated with the introduction of digital learning technologies. The positive results of digitalization of education are: the possibility of introducing new approaches, methods, models of teaching and upbringing in the educational process; the possibility of choosing an individual educational trajectory for students; increasing interest and more active involvement of schoolchildren and students in the process of obtaining and consolidation of knowledge; the ability to use a variety of mobile platforms, electronic textbooks, modern automated learning systems and augmented reality technologies that allow students to evaluate their knowledge and track their learning progress through a system of assessments and proposed test tasks.
Keywords: Digitalization of Education; Learning Technologies; Mental and Somatic Health; Coronavirus; Pandemic